Critérios de dimensionamento de biorretenções - Cadore, Regina Cera (2016)
The search for solutions in stormwater management has been a constant in human history. Being a well discussed topic nowadays, public agencies seek for quick solutions in order to minimize the catastrophes caused by floods in result to rapid and disorganized urbanization. Thus, the search for solutions in stormwater management is necessary for maintaining the quality of life, the environment and especially the preservation of the hydrological cycle. Furthermore, infiltration alternatives such as bioretention, trenches and swales have been shown as feasible and well accepted options because they minimize the negative effects of urbanization seeking to restore the natural water cycle. In Brazil, there are few studies focused on design criteria, operation and service-life of these structures, which are important data for the scale of a bioretention otherwise, would be leading to an oversized, costly and underused construction. The main purpose of this study is to analyze the sizing criteria for bioretention systems proposing suggestions for its implementation in the geomorphological conditions of the Santa Maria / RS region. The research evaluates the infiltration structure built in 2010 at the Universidade Federal de Santa Maria (UFSM). The performance of two sizing methodologies was analyzed and the dimensions were compared to the dimensions of the structure implemented at UFSM. The methodology consists of collecting infiltration data from infiltration tests recommended by NBR 13969/97, with some modifications in order to simulate a real event, data of monitoring bioretention at UFSM from 2011 to 2013, and data obtained in the stress test applied to the structure in December 2015. From these data, Horton infiltration curves for the average conditions were adjusted and inserted into the concept of unit infiltration rate (mm.h-1.m-2).The sizing was based on the analyzed methodologies (Curve-Envelope Method and LID method), after the results were compared to the actual behavior of the real structure suggesting adjustments. The results of this study indicate that the methodologies analyzes oversize the bioretention structure. From the analysis of the built bioretention behavior history it can be concluded that despite having smaller dimensions than those obtained through other methodologies sizing, it is effective to storage the drained volume. Therefore, it is clear that the lateral area and the hydrostatic pressure are important to the functioning of the structure, but also the soil-plant relationship, with the creation of preferential paths that end up improving infiltration over the service-life. Further studies are recommended in order to incorporate these items in sizing methodologies, and monitoring of similar structures in order to determine whether the behavior presented by the bioretention is default or an exception.